EXPLORATION OF THE CROCHET TECHNIQUE INROOM DIVIDERS USING VETERBAN MATERIAL - Agustin, Dyah Anggraeni; Affanti, Tiwi Bina (Arty: Jurnal Seni Rupa, 2021)
The room divider is a created situation to produce different areas in a room. Exploration of crochet techniques using vetterban material will be applied on the middle part of the room divider. The approach method used by the thesis werethe method of creating craft art according to Gustami, which includes three stages namely exploration stage(to seeking sources of ideas, to collect reference sources, to get the solution material in the design), planning stage visualization of ideas in the form of verbal descriptions with severa ldeliberation from various aspects including material aspect, technical aspect, aesthetic aspect, aspect of function and achieved in the form of 6 alternative sketches), embodiment stage (transforming1 alternative sketch into a work). Results of the exploration of the crochet technique in room dividers using veterban material, consist of 3 room dividing parts, plane 1 and 3 have the same design, plane 2 in the middle has a different plane. The colors used are bright colors.